Economic evaluation of different irrigation systems for wheat production in Rechna Doab, Pakistan - Bakhsh, A.; Ashfaq, M.; Hussain, M.; Rasool, G.; Haider, Z.; Faraz, R.H. (International Food Policy Research Institute, 2015)
Water productivity (WP) is reported lower in Pakistan when compared to the rest of the world. This paper investi-gates the factors responsible for low water productivity and demonstrates various irrigation techniques farmers could use for its improvement. A comprehensive questionnaire was designed, and 230 farmers were interviewed in a cotton-wheat area (Samundri-site I), a mixed crop area (Chiniot-site II), and a rice-wheat area (Hafizabad-site III) in Rechna Doab, Punjab, Pakistan. This survey found that the majority of farmers expressed major concerns about shortages of canal water, energy, and fertilizer. These issues were the main factors affecting their land and water productivity. Field experiments were conducted at the above mentioned sites. The results indicated that drip irrigation was the most efficient irrigation technique, which produced a maximum WP of 2.26 kg m-3 for wheat. Drip irrigation was 98% efficient, and water savings were 40% better when compared with that under conventional irrigation.